Five seasons dynamic of adaptability united latent quality indicator of Deschampsia antarctica (Poaceae) population of Galindez Island (Argentine Islands, maritime Antarсtic) - Miryuta, N.; Parnikoza, I.; Oliinyk, M.; Smetana, E.; Myryuta, G.; Poronnik, O.; Kunakh, V. (Ukrainian Antarctic Journal, 2017)
Main objective of the study has been complex adaptability dynamics characterization of Deschampsia antarctica (Poaceae), Galindez Island, maritime Antarctic during five summer seasons. Methods. For each of the studied populations stuff the cover of D. antarctica as vertical (upright) projection of green plant parts on the ground surface was measured using a standardized approach. Biometric parameters of all samples were measured on air-dried specimens and included: leaf length, single flower length, inflorescence length, and the number of flowers on an inflorescence. Protein densitometry profiles of seeds for studied D. antarctica populations were analyzed. To obtain a complex adaptability indicator — united latent quality indicator (ULQI) of adaptability the method of extreme grouping has been applied. The evaluation of the adaptability united latent quality indicator was performed using pairwise comparisons of the series of characteristics. Results. The trends of adaptability united latent quality indicator has been received in the stuff of six D. antarctica populations during five season. Conclusions. The nature of adaptability united latent quality indicator dynamic trend allowed to group investigated populations by form of trend to three groups: passage through maximum, passage through minimum or demonstrated oscillation process. Such individuality probably connected with microhabitat conditions. Next row addition of united latent quality indicator of adaptability dynamics would allow to confirm or reject the oscillating nature of the trend and to compare it with some climatic indicator dynamics.